Twofish cryptographic APPLICATION FOR SAFETY DATA COMPUTER - Marzuki Marzuki Marzuki (Majalah SIKOMTEK, 2005)
Twofish is a 128-bit block cipher that can accept variable length keys up to 256 bits. Cipheris a 16 round Feistel network with a bijective F function consists of four key-dependent 8-by-8-bit S-Box, a constant of 4-by-four as the maximum distance to the reference matrix areseparated on GF teripisah ( 28), a